Diversity, Equity, and Inclusion – A case of select Indian organizations - Indiran, Jayasri (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
Internationally, companies have made DEI metrics a Key Performance Indicator (KPI) and have linked executive compensation to their direct contributions. With the recent changes, due to the anti-DEI executive orders and increasing legal and political challenges, facing such initiatives of the United States of America (USA), the Diversity, Equity, and Inclusion (DEI) programs all across the globe are disrupted. Though there are studies in DEI programs, policies, and initiatives in various sectors and policy levels, very little study is done on investments. Hence, this study proposes a unique approach regarding the DEI perspectives and relevant investment policy decisions. Nifty 50, an Indian stock market Index representing the performance of the 50 largest Indian companies listed as of 17th March 2025, in the National Stock Exchange (NSE), is the sample framework from which the sample of organizations was chosen for data collection. Deductive Summative Analysis approach is used in the study. Areas such as workforce composition, inclusive compensation and benefits, millennials' induction to employment, and awareness creation still need more attention. The study was done based on available key terms from the sourced documents.